2016
DOI: 10.1038/modpathol.2015.154
|View full text |Cite
|
Sign up to set email alerts
|

Next generation sequencing of Cytokeratin 20-negative Merkel cell carcinoma reveals ultraviolet-signature mutations and recurrent TP53 and RB1 inactivation

Abstract: Merkel cell carcinoma is a rare but highly aggressive cutaneous neuroendocrine carcinoma. Cytokeratin-20 (CK20) is expressed in approximately 95% of Merkel cell carcinomas and is useful for distinction from morphologically similar entities including metastatic small cell lung carcinoma. Lack of CK20 expression may make diagnosis of Merkel cell carcinoma more challenging, and has unknown biological significance. Approximately 80% of CK20-positive Merkel cell carcinomas are associated with the oncogenic Merkel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 50 publications
(81 reference statements)
3
69
0
1
Order By: Relevance
“…Mutational load was not examined in this case. However, based on recent genomic findings in MCPyV-negative tumors, we would predict this MCPyV-negative case to display a high mutational burden with associated neoantigens that may result in susceptibility to immunotherapy [11, 19].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutational load was not examined in this case. However, based on recent genomic findings in MCPyV-negative tumors, we would predict this MCPyV-negative case to display a high mutational burden with associated neoantigens that may result in susceptibility to immunotherapy [11, 19].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Pathology demonstrated morphologic and immunohistochemical (strongly cytokeratin-20, neuron specific enolase and CD56 positive and thyroid transcription factor-1 negative) findings in both lesions consistent with MCC. Polymerase chain reaction performed on deoxyribonucleic acid extracted from formalin-fixed, paraffin-embedded tumor tissue alongside appropriate controls using a previously described protocol demonstrated that the tumor lacked detectable Merkel cell polyomavirus (MCPyV) large T antigen and small T antigen [10, 11]. Staging fluorodeoxyglucose-positron emission tomography/computed tomography (FDG-PET/CT) revealed lesions in right upper lung, right upper back, right axilla and right adrenal gland consistent with metastatic disease (Fig.…”
Section: Case Presentationmentioning
confidence: 99%
“…For 22 MCC cases from 14 unique patients, the results of MCPyV immunohistochemistry previously performed for other studies were available. 2,35,36 The SmCC cohort consisted of 61 tumours from 60 unique patients, with primary sites including lung (27), bladder (18), cervix (3), gastrointestinal tract (3), sinonasal tract (2), ovary (3), breast (1), prostate (1), thymus (1) and larynx (1). Five negative lymph nodes from non-MCC cases served as negative controls.…”
Section: Materials and Methods C A S E C O H O R Tmentioning
confidence: 99%
“…Harms et al reported that 80% of CK20-positive MCC patients were associated with MCPyV oncogenes. Next-generation sequencing techniques were used to show the presence of virus-independent mechanisms such as BAP1, or TP53 and RB1 inactivation in CK20-negative MCC patients, and were able to interpret these as findings of CK20 negativity in MCC to date [10].…”
Section: Discussionmentioning
confidence: 99%